STUDI PENGARUH PENCAMPURAN SAMPAH DOMESTIK, SEKAM PADI, DAN AMPAS TEBU DENGAN METODE MAC DONALD TERHADAP KEMATANGAN KOMPOS - Badrus Zaman; Endro Sutrisno (Universitas Diponegoro, 2007)
This research using the domestic organic garbage which is mixed by rice bran and cane pulp, with the variation of mixing pursuant to ratio C/N and moisture is, cane pulp : domestic organic garbage equal to 1:4, 2:7, rice bran : domestic organic garbage, 1:4, 2:7, and also the mixture cane pulp : domestic organic garbage : rice bran, 2:10:2, 1:7:1. Conduct attempted by aerobic and Mac Donald method. So that pursuant to the research can be taken conclusion that mixing lock up the rice bran and cane pulp with the domestic organic garbage is slow down the compost maturity so that unnecessary of cane pulp mixing and rice bran of at domestic organic garbage composting, compost quality of result of mixing as according to value of compost quality at SNI 19-7030-2004. Composition which it faster the compost maturity is control and composition which it has good ratio C/N from 6 variation is variation AS 27 which it consists of two cane pulp and seven domestic organic garbage.